2020
DOI: 10.1002/ieam.4371
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biodiversity: State‐of‐the‐Art and Possible Implementation in Chemical Risk Assessment

Abstract: Acknowledgements-The SETAC Europe Special Science Symposium (SESSS14) on Soil biodiversity was financially supported by SETAC Europe and several organizations facilitating the participation of the speakers and members of the steering committee. Roel Evens, Bart Bosveld, and all other staff of SETAC Europe are acknowledged for the smooth organization of SESSS14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Five use studies are being developed based on the results of the pesticide data: On a basic level, LUCAS Pesticides data are used to provide the most extensive quantification so far of the variation in the distribution of pesticide active ingredients and selected metabolites in agricultural topsoil of the EU. The results are expected to highlight regional patterns reflecting pesticide application practices as well as different environmental and soil characteristics. As samples taken for the analysis of pesticides overlap with those from biodiversity survey, the two datasets are combined to offer a powerful research tool for exploring ecotoxicological risks posed by pesticide residues on soil‐living communities in EU agricultural soils and possibly identify indicator species associated with specific pesticide residues (van Gestel et al, 2021). The spatial randomization of sampling sites and the random timing of sampling with respect to pesticide application (broadly corresponding to the crop growing season) imply that LUCAS data are randomly related to spatio‐temporal use patterns.…”
Section: Lucas Soil Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Five use studies are being developed based on the results of the pesticide data: On a basic level, LUCAS Pesticides data are used to provide the most extensive quantification so far of the variation in the distribution of pesticide active ingredients and selected metabolites in agricultural topsoil of the EU. The results are expected to highlight regional patterns reflecting pesticide application practices as well as different environmental and soil characteristics. As samples taken for the analysis of pesticides overlap with those from biodiversity survey, the two datasets are combined to offer a powerful research tool for exploring ecotoxicological risks posed by pesticide residues on soil‐living communities in EU agricultural soils and possibly identify indicator species associated with specific pesticide residues (van Gestel et al, 2021). The spatial randomization of sampling sites and the random timing of sampling with respect to pesticide application (broadly corresponding to the crop growing season) imply that LUCAS data are randomly related to spatio‐temporal use patterns.…”
Section: Lucas Soil Pesticidesmentioning
confidence: 99%
“…2. As samples taken for the analysis of pesticides overlap with those from biodiversity survey, the two datasets are combined to offer a powerful research tool for exploring ecotoxicological risks posed by pesticide residues on soil-living communities in EU agricultural soils and possibly identify indicator species associated with specific pesticide residues(van Gestel et al, 2021). 3.…”
mentioning
confidence: 99%
“…More commonly, such ecological indices could respond to the interaction of both and a decrease in species richness could be the cumulative result of, for instance, chemical, physical and biological stresses. Thus the choice of a control site, when possible, with overall similar characteristics with respect to the targeted ones is of primary importance in a triad procedure (van Gestel et al, 2021). Another well-represented approach in ecology LoE consisted in measuring the impact of contamination on soil functioning.…”
Section: Ecology: Approaches Used For the Ecological Characterization...mentioning
confidence: 99%
“…Several studies have shown that microplastic particles can exert their toxic effects on organisms not only directly, but also indirectly, such as via the dilution of food through or the formation of foodmicroplastic agglomerates (Hanna et al, 2018;Mueller et al, 2020;Rauchschwalbe et al, 2021). Higher-tier studies, especially terrestrial model ecosystems (TMEs), can reveal both the direct and indirect effects of microplastics on several taxa, trophic, population levels or developmental stages of organisms (Gestel et al, 2020;Mueller et al, 2020). 3) In publications dealing with chemical effects, it could be reported that the exposure time influenced the magnitude of leaching or vector impact (Xu et al, 2021b;Soroldoni et al, 2021).…”
Section: Experimental Approachesmentioning
confidence: 99%